2000
DOI: 10.1023/a:1005458919344
|View full text |Cite
|
Sign up to set email alerts
|

Compensating plaintiffs and punishing defendants: Is bifurcation necessary?

Abstract: Critics of the civil jury have proposed several procedural reforms to address the concern that damage awards are capricious and unpredictable. One such reform is the bifurcation or separation of various phases of a trial that involves multiple claims for damages. The purpose of this study was to assess the effects of bifurcating the compensatory and punitive damages phases of a civil tort trial. We manipulated the wealth of the defendant and the reprehensibility of the defendant's conduct (both sets of evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Most studies have shown that jurors award damages appropriately (Cather et al, 1996;Greene & Loftus, 1998;Greene, Woody, & Winter, 2000;Wissler, Evans, Hart, Morry, & Saks, 1997). When awarding compensatory damages to a plaintiff in personal injury, automobile negligence, medical malpractice, and insurance bad faith cases, jurors appropriately consider the plaintiff's pain and suffering (Mott, Hans, & Simpson, 2000), injury severity (Mott et al, 2000;Robbennolt & Studebaker, 1999;Wissler et al, 1997), and injury duration (Wissler et al, 1997).…”
Section: Harassment Severity and Damage Awardsmentioning
confidence: 99%
“…Most studies have shown that jurors award damages appropriately (Cather et al, 1996;Greene & Loftus, 1998;Greene, Woody, & Winter, 2000;Wissler, Evans, Hart, Morry, & Saks, 1997). When awarding compensatory damages to a plaintiff in personal injury, automobile negligence, medical malpractice, and insurance bad faith cases, jurors appropriately consider the plaintiff's pain and suffering (Mott, Hans, & Simpson, 2000), injury severity (Mott et al, 2000;Robbennolt & Studebaker, 1999;Wissler et al, 1997), and injury duration (Wissler et al, 1997).…”
Section: Harassment Severity and Damage Awardsmentioning
confidence: 99%
“…As compensatory damages are evaluated according to the seriousness of each plaintiff's injuries and are designed to furnish compensation for personal losses (Greene, Woody, & Winter, 2000), this research focuses on innovations that may assist jurors in the decision-making process associated with compensatory awards. Specifically, this study investigates the effectiveness of bottom-line expert witness summaries and note-taking as procedures that can enhance juror competence and performance when awarding compensatory damages.…”
Section: Improving Juror Cognitive Performance Via Procedural Innovatmentioning
confidence: 99%
“…Compensatory damages are awarded to recompense the plaintiff for economic and non-economic costs. In contrast, in a small percentage of trials, punitive damages are awarded based on the blameworthiness and malevolence of the defendant's behaviour (Greene et al, 2000). In this case, the trial was divided into two parts: the first concerning liability, followed by evidence on compensatory damages.…”
Section: Trial Materialsmentioning
confidence: 99%
“…At least in this domain, jurors generally apply their instructions as the law anticipates. 2 In another study, Greene, Woody, and Winter (2000) assessed whether jurors appropriately apply instructions related to punitive damages considerations. In particular, jurors are to use evidence related to the reprehensibility of the defendant's conduct and the defendant's wealth only to gauge the amount of punitive damages and are not to use this information to determine compensatory damages.…”
Section: Application Of Substantive Instructions Related To Damage Awmentioning
confidence: 99%
“…Mock jurors in the Greene, Woody, and Winter (2000) study read summaries of three cases: automobile negligence, products liability, and medical malpractice. In each case, the conduct of the defendant (mildly reprehensible vs. highly reprehensible) and the defendant's wealth (moderately wealthy vs. very wealthy) were manipulated.…”
Section: Application Of Substantive Instructions Related To Damage Awmentioning
confidence: 99%